2011
DOI: 10.1159/000330082
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Signaling Modulates AQP2 Trafficking via Arg-Gly-Asp (RGD) Motif

Abstract: Aquaporin-2 (AQP2) increases the water permeability of renal collecting ducts in response to vasopressin. Vasopressin stimulation is accompanied by a profound remodeling of actin cytoskeleton whose dynamics are regulated by crosstalk between intracellular and extracellular signals. Here, we report that AQP2 contains a conserved RGD domain in its external C-loop. Co-immunoprecipitation experiments demonstrated that AQP2 binds integrin β1 in renal tissue and in MCD4 cells. To investigate the role of this interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 59 publications
(69 reference statements)
2
53
0
1
Order By: Relevance
“…Biocytin hydrazide was used to label apical membrane proteins following the method of Tamma et al (13) with modifications. Briefly, the apical plasma membrane of the cells were treated with sodium periodate, which oxidizes the glycan of the apical membrane proteins before biocytin hydrazide labeling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocytin hydrazide was used to label apical membrane proteins following the method of Tamma et al (13) with modifications. Briefly, the apical plasma membrane of the cells were treated with sodium periodate, which oxidizes the glycan of the apical membrane proteins before biocytin hydrazide labeling.…”
Section: Methodsmentioning
confidence: 99%
“…However, several technical barriers prohibited deeper quantitative analysis: (i) labeling of the apical plasma membrane of native collecting ducts required technically difficult perfusion of the biotinylation reagent into the collecting duct lumens; (ii) AQP2, the major vasopressin target, was not efficiently biotinylated because it has only one extracellular NHS-reactive lysine that is likely occluded by an adjacent N-glycosylation site in the second extracellular loop; and (iii) investigation of native collecting ducts precluded the use of in vivo metabolic labeling for accurate quantification of protein abundance changes. In this study, we overcame these limitations by using stable-isotope labeling with amino acids in cell culture (SILAC) methodology in cultured mouse cortical collecting duct (mpkCCD-clone 11) cells (4) that had undergone apical surface biotinylation with a reagent that targets extracellular N-glycosyl groups (13). Biotinylated proteins were identified…”
mentioning
confidence: 99%
“…They showed that AQP2 interacts with integrins through the integrin-binding site in AQP2, Arg-Gly-Asp (RGD), which is the same motif identified by Tamma et al 10 They then observed that AQP2 promotes epithelial cell migration, which is an important mechanism of tissue repair following injury, in both MDCK and LLC-PK1 cells, and that promigration effects requires both AQP2 and b1 integrin. Finally, they proceeded to show that AQP2 promotes epithelial cell migration by facilitating the turnover of b1 integrin in the focal adhesions.…”
mentioning
confidence: 75%
“…In addition, Tamma et al 10 recently showed that integrin signaling modulates AQP2 trafficking. This suggested to Chen et al that an interaction between AQP2 and an integrin at this site may contribute to the tubular abnormalities seen in AQP2-null mice.…”
mentioning
confidence: 99%
“…tert-Butyl hydroperoxide (tBHP) was kind gift from A. Signorile (University of Bari). To immunoprecipitate and detect the total amount of AQP2, we used antibodies (Pre-C-tail Ab) against the 20-amino acid residue segment just N-terminal from the polyphosphorylated region of AQP2 (CLKGLEPDTDWEEREVRRRQ) (11). Alternatively, AQP2 was detected using a specific antibody (C-tail Ab) raised against a synthetic peptide corresponding to the last 15 C-terminal amino acids of human AQP2 (12).…”
Section: Methodsmentioning
confidence: 99%